PROFITABILITAS BERPERAN SEBAGAI MODERATING VARIABEL : PENGARUH STRUKTUR MODAL DAN HARGA SAHAM TERHADAP FIRM VALUE (STUDI EMPIRIS PADA PERUSAHAAN SUB SEKTOR PERBANKAN DI BURSA EFEK INDONESIA TAHUN 2018-2022) - Erianto; Pratiwi, Adhytia Putri (Publika Citra Media, 2025)
The purpose of this study was to determine the effect of Capital Structure and Stock Prices intensity Firm Value with Profitability as a moderating variabel. This study uses a sample of Banking companies listed on the Indonesia Stock Exchange in 2018-2022. The data used in this study are financial reports and annual reports. The sampling tecnique used was Purposive Sampling. The population used in this study were 47 banking companies with a sample of 27 banking companies selected with a total sample of 135 data. To test the hypothesis carried out with a significance test, namely the F tes, t test and Moderated Regresion Analysis (MRA) test with a significance level of 5%. Data processing used eviews 10. The results of this study indicate that Capital Structure has effect on Firm Value, and Stock Prices have an effect on Firm Value. Mean while, Capital Structure and Stock Price simultaneously affect Firm Value. Research result profitability can as a moderating variable the influence of Capital a Structure on Firm Value, and Profitability as a moderating variable can moderate the influence of Stock Price on Firm Value.